THE EFFECT OF FOREIGN AND DOMESTIC INVESTMENTS ON THE EMPLOYMENT AVAILABILITY IN INDONESIA - Steven Steven (Omnibus Law Journal, 2021)
Investment in developed countries is one of the things that is taken into account for the economic development of the country. Therefore, the state/government has a reason to regulate the dynamics of investment. The presence of investors in Indonesia is one of the important factors in the development of the national economy, it has been proven that many industries and companies have used this institution as a medium to absorb investment and the media to strengthen their financial position. Investment itself is all forms of investment activities, both by domestic investors and foreign investors or better known as PMA. The activity itself uses funds originating from these investors into economic activities. In Law Number 25 of 2007 concerning Investments The existence of investors in Indonesia is one of the important factors in the development of the national economy, it has been proven that many industries and companies have used this institution as a medium to absorb investment and the media to strengthen their financial position. If these companies can expand, the availability of job opportunities will be even wider. Given, these companies will certainly get enough capital to buy supporting production activities. Not only that, these companies will certainly need workers because the scale of production activities is getting bigger. Therefore, this paper intends to identify the effect of the capital market on job availability in Indonesia. Keywords: foreign, domestic, investment, employment